Is there a place for a molecular diagnostic test for pelvic inflammatory disease in primary care? An exploratory qualitative study - Helen Bittleston; Jane S. Hocking; Jane L. Goller; Jacqueline Coombe; Deborah Bateson; Sally Sweeney; Kirsteen Fleming; Wilhelmina M. Huston (PLoS ONE, 2022)
Introduction There is currently no test for pelvic inflammatory disease (PID) that is non-invasive and sufficiently sensitive and specific. Clinicians must therefore diagnose PID clinically, ruling out medical emergencies and conducting pelvic examinations where possible. While guidelines state that clinicians should be prepared to over-diagnose PID, it remains an under-diagnosed condition, with severe reproductive health impacts when left untreated. This research is the first to consider the perspectives of end-users on the development of a diagnostic test for PID. Methods Semi-structured live video feed online (Zoom) interviews were conducted with 11 clinicians and nine women (aged 18–30 years) in Australia to understand how a diagnostic test might be used, and what characteristics a test would need for it to be acceptable to clinicians and young women. Participants were recruited via researcher and university student networks. Reflexive thematic analysis was used to identify key themes relating to the acceptability and characteristics of a diagnostic test for PID. Results Seven general practitioners, four clinicians working in sexual health clinics, and nine young women (aged 21–27 years) were interviewed. Clinicians were aged between 31–58 years and were predominantly female. Clinicians recognised that the development of an accurate test to diagnose PID would be valuable to themselves and other clinicians, particularly those who lack experience diagnosing PID, and those working in certain settings, including emergency departments. They discussed how they might use a test to enhance their clinical assessment but highlighted that it would not replace clinical judgement. Clinicians also considered how a test would impact the patient experience and time to treatment, emphasising that it should be minimally invasive and have a quick turnaround time. Young women said a test would be acceptable if endorsed by a trustworthy clinician. Conclusions PID remains a challenging diagnosis. Development of a minimally invasive and sufficiently accurate diagnostic test would be acceptable to young women and benefit some clinicians, although no test would completely replace an experienced clinician’s judgement in making a PID diagnosis.